Deep-water continental margins: geological and economic frontiers - Alves,TM; Bell,RE; Jackson,CA-L; Minshull,TA (Basin Research, 2014)
Deep-water margins have been the focus of considerable research during the past decade. They comprise vast, underexplored regions, in which only recently have improvements in seismic imaging and drilling technology allowed the discovery of significant hydrocarbon accumulations. This volume comprises of a series of manuscripts based on studies from continental margins bordering India, East Africa, Australia, China, Norway, the United Kingdom, Iberia, Newfoundland, the southern US, West Africa and Brazil, thus offering a global perspective on the evolution and economic significance of deep-water margins. The articles in this volume examine: (i) the quantification of extension and hyperextension in distal parts of continental margins, and their relationship with regional subsidence, (ii) the importance of magmatism in the structural and thermal evolution of rifted continental margins, (iii) the processes driving and the significance of regional exhumation during and after syn-rift stretching, (iv) the tectonic setting of salt basins and (v) depositional patterns along deep-water margins. To complement this work, we present a personal view of some of the specific questions that need to be addressed in the next few years of deep-water continental margin research.